SISTEM KONTROL OTOMATIS PENGISIAN TANGKI BBM DAN MONITORING SUHU MENGGUNAKAN PLC - Sonny Rumalutur; Alimuddin Mappa; Erwin P Sianipar (Electro Luceat, 2020)
Fuel oil reservoir filling and temperature monitoring can be done automatically using Omron PLC type CP1E N20DR-D 20 I / O with a ladder diagram program designed with the CX-Programmer computer application. And the input used in the form of a level sensor module and temperature sensor, while for the output in the form of a selenoid valve, 3 phase AC motor and buzzer. The level sensor functions to find out the high and low levels of the oil surface in the tank and the output is in the form of a selenoid valve module that functions as a valve for filling full oil, while the motor pump functions as a distributor fuell oil. And the temperature sensor module serves to detect the high and low temperatures or safe temperatures that are allowed at the time of distribution of fuel to the Truck fuel oil reservoir, while the output is in the form of a buzzer that serves as a source of sound or alarm markers. Based on the calculation results obtained that the error presentation of the two selenoid has the same value of 0%, while the level sensor, thermal sensor, and pump motor each have a presentation value that is almost the same with each other, so that the automatic control system of filling the fuel oil reservoir and monitorn the temperature can run smoothly.